Perancangan Website Pondok Permata Homestay Sebagai Media Informasi Dan Promosi - Sudana, Dhana; - AKPAR BSI Yogyakarta, Atun Yulianto (APMMI - Asosiasi Profesi Multimedia Indonesia, 2017)
Abstract - The development of tourism business in Bali has reached the highest point, especially the hotel business and lodgings. This matter is very possible if supported by a web-based marketing facility. Website is a media information which offers various facilities in presenting information and promotions. However, not all hotel accommodation and lodging have a website as a medium for information and reservations, One of which is Pondok Permata Homestay Ubud Bali. The difficulty of marketing the rental room accommodation and tour package because it is not presence support web-based marketing system become the reason design website Pondok Permata Homestay. Research Methods in designing websites Pondok Permata Homestay using qualitative descriptive methods for data collection. While this website application design program using Adobe Dreamweaver as a web application editor, XAMPP as localhost server and MySQL as its database. Designed this website consisting of several pages including the main page, profile, accommodations, tour and travel, facilities and services, gallery, contacts, guestbook, cafe, interesting sights and also booking. The design of the website is made complete as possible to provide information and promotions with special facilities reservation menu for the public, so as to increase the amount of guests Pondok Permata Homestay. Keywords: website design, media information and reservations. Abstrak - Pengembangan bisnis pariwisata di Bali telah mencapai titik tertinggi, terutama bisnis hotel dan penginapan. Hal ini sangat mungkin karena didukung oleh fasilitas pemasaran berbasis web. Website adalah media informasi yang menawarkan berbagai kemudahan dalam menyajikan informasi dan promosi. Namun, tidak semua akomodasi hotel dan penginapan memiliki website sebagai media informasi dan pemesanan, salah satunya adalah Pondok Permata Homestay Ubud Bali. Sulitnya memasarkan akomodasi kamar dan paket tour homestay karena tidak adanya dukungan sistem pemasaran berbasis web sehingga menjadi alasan penulis membuat desain website Pondok Permata Homestay. Metode penelitian dalam merancang website Pondok Permata Homestay menggunakan metode deskriptif kualitatif untuk pengumpulan data. Sementara program desain aplikasi website menggunakan Adobe Dreamweaver sebagai editor aplikasi web, XAMPP sebagai server localhost dan MySQL sebagai database-nya. Rancangan website ini terdiri dari beberapa halaman termasuk halaman utama, profil, akomodasi, tour dan travel, fasilitas dan layanan, galeri, kontak, buku tamu, cafe, tempat wisata yang menarik dan juga pemesanan. Desain website ini dibuat selengkap mungkin untuk memberikan informasi dan promosi dengan fasilitas khusus pada menu reservasi untuk publik yang akhirnya diharapkan dapat meningkatkan jumlah tamu Pondok Permata Homestay. Kata kunci: desain website, media informasi dan pemesanan